Labor market adjustment to import competition: Long-run evidence from establishment data - Juan S. Blyde; Matias Busso; Dario Romero Fonseca (Inter-American Development Bank (IDB), 2020)
We analyze how local labor markets in Mexico adjusted in response to an increase in Chinese import competition between 1998 and 2013. We exploit the spatial variation in import exposure arising from initial differences in industry specialization. We found that the adjustment took various forms: a decline in the number of wage employees, the substitution of some wage employees by contract workers, and the substitution of formally contracted employees by informally contracted ones. The reduction in employment levels was accompanied by an increase in the population that exited the labor force. The negative employment impact was three times more severe on production workers than on nonproduction workers, indicating that workers with lower skills were more severely affected. Overall, we find significant job losses to the order of 7.6% of the working-age population.
Keywords: F14; F16; J23; 330; Import competition; local labor markets; employment; China; Mexico